2019
DOI: 10.1186/s13046-019-1185-0
|View full text |Cite|
|
Sign up to set email alerts
|

Contributions of T cell dysfunction to the resistance against anti-PD-1 therapy in oral carcinogenesis

Abstract: Background Programmed death 1 (PD-1) blockade has great effect in the prevention of oral precancerous lesions, but the drug resistance has also been observed. The determinants of immune resistance during the malignant transformation are poorly understood. Methods Anti-PD-1 antibody was administered in the 4NQO-induced carcinogenesis mouse models. The mice were then subdivided into PD-1 resistance(PD-1R) group and PD-1 sensitive(PD-1S) group according to the efficacy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Harvested oral lesions for hematoxylin and eosin (H&E) staining and IHC were stained as previously described (Wen et al 2019). Samples for immunofluorescence (IF) were embedded in OCT compound (Sakura Tissue-Tek) and sectioned into 8-µm sections.…”
Section: Tissue Preparation Histology and Immunostainingmentioning
confidence: 99%
“…Harvested oral lesions for hematoxylin and eosin (H&E) staining and IHC were stained as previously described (Wen et al 2019). Samples for immunofluorescence (IF) were embedded in OCT compound (Sakura Tissue-Tek) and sectioned into 8-µm sections.…”
Section: Tissue Preparation Histology and Immunostainingmentioning
confidence: 99%
“…We speculated that there may be a relationship between mutations of the PHA02927 domain in the CSMD1-mut samples and the enrichment of the above immune signaling pathways, the infiltration of anti-tumor immune cells, and the upregulation of PD-L1, which was related to the relatively good prognosis of patients with gastric cancer. In addition, Treg cells not only play a suppressive role in anti-tumor immunity but also may participate in anti-PD-1/PD-L1 resistance mechanisms [24,25]. Patients with CSMD1-mut had less Treg cells and higher PD-L1 expression, which helped them benefit more from anti-PD-L1 and to less likely develop drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] However, Wen et al found that the PD-1 mAb was less than 70% effective in treating oral precancerous lesions. 22 Levingston and Young found that the PD-1 mAb was temporarily effective in low-grade precancerous lesions and was significantly invalid in high-grade precancerous lesions to carcinoma in situ. 23 These studies basically confirmed that there was immune escape at the stage of OL or precancerous lesions.…”
Section: Introductionmentioning
confidence: 99%